Pembatalan Perkawinan yang Daluwarsa menurut Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan: Studi Putusan Nomor 1/Pdt.G/2021/PA.Pbr - Gusdiawan Gusdiawan; Mardalena Hanifah; Dasrol Dasrol (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This research examines a case of marriage annulment filed at the Pekanbaru Religious Court, where the plaintiff, a Marriage Registrar, received a complaint from a legal wife who did not consent to her husband's marriage to another woman. The plaintiff questioned whether the annulment request had exceeded the expiration period. The study aims to (1) understand the legal consequences of filing for annulment after the legal deadline based on Marriage Law Number 1 of 1974 and Decision Number 1/Pdt.G/2021/PA.Pbr, and (2) explore the relevance of utility theory in the court’s reasoning. This is a sociological legal study using interviews and literature reviews, supported by primary, secondary, and tertiary data. The analysis uses a qualitative descriptive approach with deductive reasoning. The results show that the court granted the annulment despite the expiration, based on the discovery of an invalid guardian and procedural flaws. A verstek (default) decision was made as both defendants were absent at the first hearing. The court's decision reflects the balance of legal certainty, justice, and utility. The legal consequences include the termination of the marriage, the recognition of the child as legitimate, and the absence of shared property division.